Is China climbing up the quality ladder? Estimating cross country differences in product quality using Eurostat's COMEXT trade database - Gabor Pula; Daniel Santabárbara (European Central Bank (ECB), 2011)
There is an ongoing debate in the literature about the quality content of Chinese exports and to what extent China imposes a threat to the market positions of advanced economies. While China's export structure is very similar to that of the advanced world, its export unit values are well below the level of developed economies. Building on the assumption that unit values reflect quality the prevailing view of the literature is that China exports low quality varieties of the same products than its advanced competitors. This paper challenges this view by relaxing the assumption that unit values reflect quality. We derive the quality of Chinese exports to the European Union by estimating disaggregated demand functions from a discrete choice model. The paper has two major findings. First, China's share on the European Union market is larger than would be justified by its relatively low average prices, implying that the quality of Chinese export products is relatively high compared to many competitors. Second, China has gained quality relative to other competitors since 1995, indicating that China is climbing up the quality ladder. The relatively high and improving quality of China's exports may be explained by the increasing role of global production networks in China.
Keywords: F1; F12; F14; F15; F23; 330; Chinese Exports; COMEXT database; Discrete Choice Model; Global Production Networks; Quality Ladder; Vertical Product Differentiation; Produktqualität; Produktdifferenzierung; Internationale Arbeitsteilung; Unternehmensnetzwerk; Diskrete Entscheidung; Logit-Modell; China; EU-Staaten